Sequential circuit design using Quantum-dot Cellular Automata (QCA) - Lim L.A.; Ghazali A.; Yan S.C.T.; Fat C.C. (2023)
As the size of CMOS transistors keep shrinking, it will eventually hit its limitation. Hence, an alternative device has to be discovered to continually improve the development of electronics devices. Quantum-dot cellular automata (QCA), is a potential device that can be used to implement digital circuits. In this paper, we present the basic theory of QCA cell and some fundamental gates of QCA scheme. The fundamental gates, such as the QCA inverter and QCA majority gate are then used to build more complex logic circuits. Several design of sequential circuits such as gated D latch, RS latch, JK flip-flop, T flip-flop, D flip-flop, 2-bit counter, 4-bit counter, and 4-bit shift register are presented in QCA architecture. These designs are captured and simulated using a design software called QCADesigner. 2012 IEEE.